Ribophorin II promotes the epithelial–mesenchymal transition and aerobic glycolysis of laryngeal squamous cell carcinoma via regulating reactive oxygen species-mediated Phosphatidylinositol-3-Kinase/Protein Kinase B activation. Issue 3 (1st March 2022) - Zhou, Jingchun; Zhang, Jingjing; Zhang, Wei; Ke, Zhaoyang; Lv, Yanlu; Zhang, Bo; Liao, Zhifang
ABSTRACT: Ribophorin II (RPN2), a part of an N-oligosaccharyl transferase complex, plays vital roles in the development of multiple cancers. Nevertheless, its biological role in laryngeal squamous cell carcinoma (LSCC) remains unclear. The RPN2 expression levels in LSCC tissues and cell lines (AMC-HN-8 and TU212) were measured using real-time PCR, immunohistochemistry, or Western blot. The influences of RPN2 on the proliferation, migration, epithelial–mesenchymal transition, and aerobic glycolysis of LSCC cells were investigated after upregulation or downregulation of RPN2 in vitro and in vivo . Mechanically, we assessed the impact of RPN2 on the reactive oxygen species (ROS)/Phosphatidylinositol-3-Kinase (PI3K)/Protein Kinase B (Akt) signaling pathway. We found that compared with the control, RPN2 was highly expressed in LSCC tissues and cells. Overexpression of RPN2 elevated the proliferation, migration, glucose uptake, lactate production release, and levels of Vimentin, hexokinase-2 (HK-2), pyruvate dehydrogenase kinase 1 (PDK1), lactate dehydrogenase A (LDHA), and ROS, but inhibited E-cadherin expression in AMC-HN-8 cells. Knockdown of RPN2 in TU212 cells showed opposite effects on the above indexes. Meanwhile, RPN2 upregulation increased the levels of p-PI3K/PI3K and p-Akt/Akt, which were attenuated by N-acetyl-L-cysteine (NAC), an ROS inhibitor. Both NAC and PI3K inhibitor LY294002 could reverse the effects of RPN2 overexpression on the malignant phenotypes of LSCC cells. In xenografted mice, silencing RPN2 expression reduced tumor growth, ROS production, and levels of Ki-67, Vimentin, LDHA, and p-Akt/Akt, but enhanced E-cadherin expression. In conclusion, our data suggested that RPN2 promoted the proliferation, migration, EMT, and glycolysis of LSCC via modulating ROS-mediated PI3K/Akt activation. Graphical abstract: uf0001